PELAKSANAAN PUBLIC RELATIONS DI SMK SWASTA SE-KECAMATAN PADANG BARAT - Tia Ayu Ningrum (Jurnal Bahana Manajemen Pendidikan, 2014)
The goal of the research is to collect information about the actuating of public relations in private Senior vocational schools. The population of the research is all of principals, vice principals teachers, employees andmembers of student body at schools.The sample is 77 people, taken by disproportionate stratified random sampling technique. The instrument of the research is question with Likert scale models that had been tested for validity and reliability. Data analyzed using persenatation score and performance level. The result of this research show that the public relations in private SMK is not good. Key word : Public Relations